GAMBARAN KINERJA DI SUB BAGIAN PERBEKALAN UMUM DAN INVENTARIS RSI SURABAYA JEMURSARI - Anindi Dwi Afida,; Agus Aan Adriansyah, (Jurnal Cakrawala Ilmiah, 2023)
Logistics management is the process of planning, implementing and controlling the processes of logistics activities starting from procurement, storage, disposal and distribution to meet customer needs. The RSI Surabaya Jemursari logistics distribution system has been running effectively, but every month there are still staff errors during ANFRA services, resulting in differences between goods and data when doing stock taking at the end of the month. This study aims to analyze the factors that influence the occurrence of stockouts at RSI Surabaya Jemursari. This research is a descriptive research with cross sectional research. The variables studied consisted of planning, acceptance, distribution, deletion. The results of the discussion as a whole, the conclusions obtained by the researcher can be described that the inventory system of the logistics function at RSI Surabaya Jemursari has been running effectively. However, it needs to be improved when ANFRA's services are more thorough so that there are no errors in picking up goods which result in differences in the goods in the warehouse with the existing data.